Multi-taxa consequences of management for an avian umbrella species. (August 2019) - Hawkes, Robert W.; Smart, Jennifer; Brown, Andy; Jones, Helen; Lane, Steve; Wells, Doreen; Dolman, Paul M.
Abstract: Whether management for so-called umbrella species actually benefits co-occurring biota has rarely been tested. Here, we studied consequences for multiple invertebrate taxa of two ground-disturbance treatments designed to support an avian umbrella species (Eurasian stone-curlew, Burhinus oedicnemus ), and whether analysing ecological requirements across the regional species pool predicted beneficiaries. Responses were assessed for the abundance of five bird species of conservation concern, and the abundance, species richness and composition of carabids, staphylinids, other beetles (non-carabid, non-staphylinid), true bugs and ants, sampling 31, 258 individuals of 402 species in an extensively-replicated experiment across the UK's largest grass-heath. Both treatments provided suitable habitat for the umbrella species, in contrast to controls. Treatment influenced the abundance of only one bird species; but carabid, other beetle and ant richness increased with one or both treatments, whilst staphylinid richness and abundance increased and true bug richness and abundance decreased with both treatments. Richness of 'priority' (rare, scarce or threatened) invertebrates a priori considered to share ecological requirements with the umbrella species (predicted beneficiaries) increased with both treatments. Resampling and rarefaction showed landscapes diversified by treatment supported a greater cumulative species richness of other beetles, ants and true bugs, and importantly priority invertebrates, than a landscape comprising only untreated controls. Such experiments provide strong evidence to assess co-benefits of umbrella species management, but are costly and time consuming. The systematic examination of the autoecological requirements of co-occurring taxa (the 'Biodiversity Audit Approach') successfully predicted likely beneficiaries. Demonstrating wider biodiversity benefits strengthens the case for avian conservation management. Highlights: Umbrella species conservation tested through an extensively replicated experiment Sampling 30, 000 invertebrates revealed contrasting taxonomic responses to management. Richness of priority species with similar requirements to the umbrella increased. Diversifying the landscape through management is better than status quo. Biodiversity auditing can successfully predict the outcome of umbrella management.